Combination of magnetically actuated flexible graphite–polymer composite cathode and boron-doped diamond anode for electrochemical water softening or wastewater treatment. (10th September 2020) - Muddemann, Thorben; Haupt, Dennis; Engelke, Martin; Sievers, Michael; Fischer, Axel; Kiefer, Carmen; Filip, Kristina; Zielinski, Oliver; Hickmann, Thorsten; Kunz, Ulrich
Highlights: Moving flexible cathode for deposit removal allows long-term water treatment. These are promising counter electrodes for water treatment applications. Degree of hardness reduction depends on reactor configuration and operation point. Artificial toilet wastewater was successfully treated for reuse as flushing water. Abstract: An electrochemical reactor based on a moving graphite–polymer composite (GPC) cathode and boron-doped diamond anode is developed and used for the electrochemical water softening and treatment of artificial vacuum toilet wastewater. The magnetically actuated cathode is designed for the in situ removal of insoluble compounds, which usually precipitate on the cathode during electrochemical water treatment processes. To obtain a suitable GPC cathode, the chemical stability and conductivity of various composites and their flexion and magnetic actuator characteristics are investigated. The most suitable GPC cathode is a 0.5 mm thick polypropylene-based composite, which presents chemical stability, the lowest resistivity of all analyzed samples (5.06 ± 1.80 mΩ cm), and enables flexions up to 2.4 mm. The water softening performance of the reactor featuring this electrode was evaluated using two configurations. Water hardness was decreased up to 72% and more than 90% in mixed and separated electrolyte modes, respectively. Further investigations demonstrate that this reactor can also be used for wastewater treatment. Artificial toilet wastewater was successfully discolored for reuse as toilet flushing water. Lastly, a treatment test over 120 h demonstrates that the magnetically actuated flexible GPC cathode removes in situ deposits on its surface and requires low maintenance. The performance of the new electrode configuration is similar to that of the state-of-the-art polarity reversal system and does not shorten the electrode service life. Graphical abstract: Image, graphical abstract